PENGARUH KONTEN LITERASI DIGITAL TERHADAP PERILAKU FOLLOWERS @LITERASIDIGITALKOMINFO - Mona Lisa; Cindoswari, Ageng Rara (Prodi Ilmu Komunikasi Universitas Putera Batam, 2025)
The rapid development of digital technology has significantly changed how young people access and manage information. Instagram, as a widely used social media platform, is strategically used by government agencies to distribute digital literacy content, including through the @literasidigitalkominfo account. This study examines the effect of such content on the information-seeking behavior of its followers. Using a quantitative approach, the study surveyed 397 respondents selected with Slovin’s formula. Data were analyzed with simple linear regression. A structured questionnaire based on a 5-point Likert scale was tested for validity, reliability, and classical assumptions. Results show that digital literacy content positively and significantly influences information-seeking behavior, with a regression coefficient of 0.501 and an R Square of 0.555. This indicates that 55.5% of the behavior variation can be explained by the content’s credibility, shareability, appeal, and relevance. These findings highlight the importance of strategic digital content in encouraging followers to engage actively in information seeking—starting from initiation to focus formulation. The study supports the applicability of New Media Theory and Information Seeking Theory in understanding digital behavior in the modern media landscape. Keywords: digital literacy content, behavior of followers, new media, Instagram @literasidigitalkominfo, information seeking